A new genus and nine new species of Neotropical spittlebugs (Hemiptera, Cercopidae, Tomaspidinae) - Carvalho,Gervasio S. (2004)
The following new taxa of South American Cercopidae are described: Ferorhinella gen. nov., with type species Sphenorhina brevis Walker, 1851; Deois (Deois) knighti sp. nov. (Brazil), Deois (Deois) sexpunctata sp. nov. (Brazil), Deois (Pandysia) constricta sp. nov. (Brazil), Mahanarva (Ipiranga) bahiaensis sp. nov. (Brazil), Maxantonia bifurcata sp. nov. (Brazil), Neosphenorhina curvipenis sp. nov. (Brazil), Sphenorhina brevispina sp. nov. (Ecuador), Sphenorhina nigricephala sp. nov. (Ecuador), Sphenorhina minuta sp. nov. (Brazil), Tropidorhinella onorei sp. nov. (Colombia), Zuata luteofascia sp. nov. (Colombia). Ferorhinella brevis (Walker, 1851) comb. nov. In addition, descriptions are given for a new colour form of Mahanarva (M.) phantastica (Breddin, 1904) and a newly found variation in the male genitalia of Deoisella fasciata Costa & Sakakibara, 2002.